Corporate Social Responsibility on Firms’ Financial Performance: Evidence of Banking Sectors of Nepal - Wagle, Sudip (Journal of Balkumari College, 2020)
The purpose of this study was to find the trend and relationship of Corporate Social Responsibility (CSR) practices and Firm’s Financial Performance of Commercial Banks in Nepal. CSR became a mandatory issued in Nepal. Based on gaps in the extant literature, the current study hypothesizes that three dependent variables of financial performance i.e. Return on Assets (ROA), Return on Equity (ROE) and Net Income (NI) on the independent variable CSR. Out of listed 27 Commercial banks, the sample includes only 3 banks for the base of extensively disclosing CSR activities, from earlier than issued mandatory laws in Nepal. Four years of data (2015/16 to 2018/19) were collected for the study purposes. Data analyzed and interpreted using Statistical Package for Social Science (SPSS) Specifically Pearson’s Correlation to analysis the relationship between CSR disclosure activities and Financial Performance. The results revealed that out of 3 variables only a CSR activity on ROA is significantly accepted with having a negative correlation among them. Moreover, CSR activity on ROE & CSR activity on NI both are insignificant, having a neutral relationship i.e. rejected.